Incidence of Chronic Kidney Failure and Alcohol Consumption: Meta Analysis - Atmojo, Joko Tri; Yuliyanto, Dwi Joko; Hasanah, Yesi Ihdina Fityatal; Widiyanto, Aris; Anasulfalah, Hakim; Mubarok, Ahmad Syauqi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
One of the main risk factors for chronic kidney disease (CKD) is excessive alcohol consumption. Alcohol consumption can damage the kidneys and disrupt their function because the kidneys filter toxins and waste products from the blood. This study aims to estimate the magnitude of the relationship between alcohol consumption and the incidence of chronic kidney failure. This research is a systematic review and meta analysis with PICO as follows, population: Adults. Intervention: alcohol consumption, Comparison: no alcohol consumption. Outcome: chronic failure events. The articles used in this research were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are